1988
DOI: 10.1111/j.1755-3768.1988.tb04060.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear cataract ‐ a microradiographic study

Abstract: Abstract. Nuclear cataract is a common type of senile cataract characterized by an increased turbidity and often a yellow to brown pigmentation of the nucleus. Twenty‐one human lenses with different degrees of nuclear turbidity were, after intracapsular cataract extraction, examined by a quantitative microradiographic technique. The dry mass concentration was determined along the lens axis, and revealed an overall distribution similar to the normal lens. The concentration increased from the poles towards the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Cells located in the center of the lens have significantly higher protein contents than those situated near the surface. 25 Paralleling this protein gradient is a refractive index gradient 26 that serves to correct longitudinal spherical aberration. Despite its central importance to the optics of the eye, little is known about how the refractive index gradient is generated in the lens and adjusted over the lifespan to match the refractive needs of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…Cells located in the center of the lens have significantly higher protein contents than those situated near the surface. 25 Paralleling this protein gradient is a refractive index gradient 26 that serves to correct longitudinal spherical aberration. Despite its central importance to the optics of the eye, little is known about how the refractive index gradient is generated in the lens and adjusted over the lifespan to match the refractive needs of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…Older studies have suggested that light toxicity, oxidation of lens proteins, use of intraocular gas, and length of operative time may be causative factors (Cherfan 1991; de Bustros 1988; Ogura 1991). Newer research suggests that vitrectomy surgery increases oxygen tension within the eye; oxygen exposure has been linked with progressive nuclear sclerotic cataract formation (Holekamp 2005; Palmquist 1988). …”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggests that underlying reasons might include light toxicity, excessive oxygenation of lens proteins, gas endotamponade and prolonged time of surgery [1][2][3][4]. Many studies suggest that PPV may contribute to increased intraocular oxygen pressure and that oxygen exposure leads to progressive cataract formation [5,6].…”
mentioning
confidence: 99%